Development of a best-practice clinical guideline for the use of bleomycin in the treatment of germ cell tumours in the UK. Issue 9 (30th October 2018) - Watson, Robert; Peña, Hugo; Tsakok, Maria; Joseph, Johnson; Stoneham, Sara; Shamash, Jonathan; Joffe, Johnathan; Mazhar, Danish; Traill, Zoe; Ho, Ling-Pei; Brand, Sue; Protheroe, Andrew
Abstract Bleomycin, a cytotoxic chemotherapy agent, forms a key component of curative regimens for lymphoma and germ cell tumours. It can be associated with severe toxicity, long-term complications and even death in extreme cases. There is a lack of evidence or consensus on how to prevent and monitor bleomycin toxicity. We surveyed 63 germ cell cancer physicians from 32 cancer centres across the UK to understand their approach to using bleomycin. Subsequent guideline development was based upon current practice, best available published evidence and expert consensus. We observed heterogeneity in practice in the following areas: monitoring; route of administration; contraindications to use; baseline and follow-up investigations performed, and advice given to patients. A best-practice clinical guideline for the use of bleomycin in the treatment of germ cell tumours has been developed and includes recommendations regarding baseline investigations, the use of pulmonary function tests, route of administration, monitoring and patient advice. It is likely that existing heterogeneity in clinical practice of bleomycin prescribing has significant economic, safety and patient experience implications. The development of an evidence-based consensus guideline was supported by 93% of survey participants and aims to address these issues and homogenise practice across the UK.